Investment Of Fixed Equipment Assets On Improving Profitability (case study cv.Parahyangan Express BranchKarawang) - Sri Suartini; Dian Hakip Nurdiansyah; Sheli Rosdayanti (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2020)
The purpose of this study to determine how much influence of fixed asset investment vehicles against profitability CV. Parahyangan Express Karawang Branch. This research uses a descriptive verification method with a primary data source that is a financial report CV. Parahyangan Express Karawang Branch period 2007 to 2016. The result of this research is r average investment value CV. Parahyangan Express in the period 2007 until 2016 tends to decrease, the average value of profitability CV. Parahyang n Express in the period 2007 to 2016 tends to decline. Based on test results t comparison t arithmetic with t table showing 2.840> 2.093 t count more than t table. vehicle fixed asset investment has a significant effect on profitability in a CV. Parahyangan Express. The percentage of influence of fixed asset investment of 30% means 30 % development of profitability CV. Parahyangan Express is influenced by in-kind fixed assets while 70 % is influenced by other factors not examined in this study.